Recreating Epidermolysis Bullosa Simplex in Zebrafish with Transgenesis - MacDonnell, Samuel (Université d'Ottawa / University of Ottawa, 2018)
Epidermolysis Bullosa simplex (EBS) is a rare genetic disorder that is typically inherited in an autosomal dominant fashion and affects approximately 1 out of 20 000 individuals. This disease is caused by mutations in either the KRT14, KRT5 or PLEC genes. These genes code for proteins involved in the formation of the cytoskeleton in basal keratinocytes, which form the basal layer of the epidermis. The cytoskeleton provides structural support to the basal keratinocytes and mutations in these genes cause cytoskeletal malformations, making these cells more susceptible to physical stress. This results in the cells undergoing lysis under trivial mechanical stress and causing the epidermis to detach from the dermis, the layer immediately below the epidermis. This leads to the primary symptom of EBS: the formation of blisters. The goal of this project is to recreate EBS in zebrafish using transgenesis and to create stable mutant transgenic line. In the future, high throughput drug screening will be done on mutant zebrafish embryos to find potential drug candidates that can alleviate the symptoms of EBS. To accomplish this, missense and deletion mutations in zebrafish krt5 cDNA using site-directed mutagenesis were performed. It was previously shown that mice models for this disease die shortly after birth and thus no stable mutant lines were able to be created. To ensure embryo survival and avoid a similar fate, mutant krt5 cDNA was expressed in non-essential tissue, such as the embryonic fin fold using a fin epithelial-specific enhancer named epi. These constructs were injected into one-cell stage zebrafish embryos, which were raised and screened for integration of the construct in their germ cells. While results from injected embryos were promising, mutant transgenic zebrafish did not demonstrate any blistering. In an attempt to induce blistering, mutant zebrafish embryos were placed under various environmental stressors known to worsen the symptoms of EBS. This was not successful. Expression of mutant keratin 5 in the basal epidermis of the entire embryo using the 2.3kb upstream region of the zebrafish krt5 gene to drive expression also did not yield any results. More investigations are needed to determine if it will be possible to use the zebrafish to model EBS.
Keywords: Molecular Genetics; Rare diseases